PENGARUH PEMBERIAN MIKROBA PROBIOTIK LOKAL TERHADAP PENINGKATAN PRODUKSI JAGUNG HIBRIDA - Haryati, Yati; Permadi, Karsidi (Jenderal Soedirman University, 2016)
National corn demand continues to increase every year, either for food, feed and industrial raw materials.To meet this requirement forced to do import corn because the results at the farm level is still low. One is notapplying technological innovation and resource integrated crop management (ICM). Then in an effort to increasecorn production as well need to use the local probiotic microbes allow. This study aims to determine the extent towhich the results of applying maize crop management and integrated resource ( ICM - maize) equipped with LocalProbiotic Microbial fertilizer. The assessment was conducted in the village Cicurug, Majalengka Subdistricts,District Majalengka. The study used a Randomized Block Design Complete (RCBD), four treatments with sixreplications. For the treatment of local administration of probiotic microbes, the dose of 3 l ha-1 Agri Simba, thedose of 3 l ha-1 Agri Simba + 1.500 g of urea, the dose of 6 l ha-1 Agri Simba, and a dose of 6 l ha-1 Agri Simba +3.000 g of urea. The results of the study showed that administration of probiotic microbes local (Agri Simba) hassignificant effect on growth, yield components and yield of hybrid maize varieties P-21. Yield dried shelled beanshighest achieved by the provision of local probiotic microba in the dose 6 l ha-1 + 3.000 g Agri Simba urea was12.20 t ha-1. The results obtained at the lowest dose of 3 l ha-1 Agri Simba around 8.73 t ha-1. Component resultssupport the results of the P-21 hybrid maize is a heavy cob, number of rows per ear and weight of 100 grains .Key words: Maize, Local Probiotic MicrobaÂ ABSTRAKKebutuhan jagung nasional terus meningkat setiap tahun, baik untuk pangan, pakan maupun bahan bakuindustri. Untuk memenuhi kebutuhan ini terpaksa melakukan impor jagung karena hasil di tingkat petani masihrendah. Salah satu penyebanya adalah belum optimal penerapan inovasi teknologi pengelolaan tanaman dansumberdaya terpadu (PTT). Dalam upaya peningkatan produksi jagung diperlukan juga penggunaan mikrobaprobiotik lokal. Pengkajian ini bertujuan untuk mengetahui sejauh mana hasil jagung yang menerapkanpengelolaan tanaman dan sumberdaya terpadu (PTT-jagung) yang dilengkapi dengan pemberian pupuk MikrobaProbiaik Lokal. Pengkajian iji dilaksanakan di desa Cicurug, kecamatan Majalengka, kabupaten Majalengka padaMK II. Kajian ini menggunakan rancangan acak kelompok (RAK), empat perlakuan dengan enam ulangan.Sebagai perlakuan pemberian mikroba probiotik lokal yaitu, takaran 3 l/ha Agri Simba, takaran 3 l/ha Agri Simba+ 1.500 g Urea, takaran 6 l/ha Agri Simba, dan takaran 6 l/ha Agri Simba + 3.000 g Urea. Hasil kajian menunjukkanbahwa pemberian mikroba probiotik lokal (Agri Simba) berpengaruh nyata pada pertumbuhan, komponen hasildan hasil jagung varietas hibrida P-21.Hasil pipilan biji kering tertinggi dicapai oleh pemberian mikroba probiotiklokal pada takaran 6 l/ha Agri Simba + 3.000 g Urea sebesar 12,20 t/ha. Hasil terendah diperoleh pada takaran 3l/ha Agri Simba sekitar 8,73 t/ha.Kata kunci : Jagung, Mikroba Probiotik Lokal